Tracking Affective Language Comprehension: Simulating and Evaluating Character Affect in Morally Loaded Narratives - ‘t Hart, Björn; Struiksma, Marijn E.; van Boxtel, Anton; van Berkum, Jos J. A. (Frontiers in Psychology, 2019)
Facial electromyography research shows that corrugator supercilii ('frowning muscle') activity tracks the emotional valence of linguistic stimuli. Grounded or embodied accounts of language processing take such activity to reflect the simulation or ‘re-enactment’ of emotion, as part of the retrieval of word meaning (e.g., of “furious”) and/or of building a situation model (e.g., for “Mark is furious”). However, the same muscle also expresses our primary emotional evaluation of things we encounter. Language-driven affective simulation can easily be at odds with the reader’s affective evaluation of what language describes (e.g., when we like Mark being furious). In a previous experiment (‘t Hart et al., 2018) we demonstrated that neither language-driven simulation nor affective evaluation alone seem sufficient to explain the corrugator patterns that emerge during online language comprehension in these complex cases. Those results showed support for a multiple-drivers account of corrugator activity, where both simulation and evaluation processes contribute to the activation patterns observed in the corrugator. The study at hand replicates and extends these findings. With more refined control over when precisely affective information became available in a narrative, we once again found evidence that spoke against an interpretation of corrugator activity in terms of simulation or evaluation alone; once more the multiple-drivers account seemed most plausible. We also found preliminary evidence indicative of incremental updating of the situation model, we speculate that readers appear to wait to integrate additional information regarding the emotions of immoral characters before a differential corrugator response emerges. In all, this study brings us closer to a refined understanding of online affective language comprehension and offers insights regarding the real-time integration of reader’s evaluative responses to affective information in an unfolding narrative.